Intensifying the exercise using a device to control the angles of muscle work in developing the chest muscles and maximum strength for bodybuilding players - Abdulrahman , Ameer; Rashid , Ammar; Khamis , Hussein (Journal of Physical Education, 2024)
The significance of the research emerged through the development of certain muscle groups (chest muscles and maximum strength) in the sport of bodybuilding, which requires intensive exercises using a device that controls the angles of muscle work. This device greatly contributes to creating a qualitative training breakthrough that aligns with the demands of bodybuilding by determining the movement path of the exercise to achieve the goal the researcher aims to explore in using the muscle angle control device. The focus is precisely on this in exercises to develop certain muscle groups (chest muscles and maximum strength) so that they harmonize with the development objective. As for the research problem, there is fatigue or a drop in effort in specific parts during the exercise’s movement path. This involves performing traditional exercises that have been in practice for many years across all bodybuilding exercises. The transition in the amount of effort exerted on the muscle along the range of motion for the involved body parts is required to address the state of fatigue and reduced effort in those parts, which demands greater muscle pressure in each exercise according to the working muscles. The result of this is to generate an intensification of the effort exerted on the muscle. Since the researchers work in training and development by supervising the training of many athletes practicing this sport, it was found important to move towards designing an innovative device that demonstrates control of muscle work angles in executing exercises. This is something not currently available in the Iraqi, Arab, or global training environments specialized in bodybuilding